Criminalizing Domestic Violence in Egypt: Legal Gaps, Risk Consequences, and the Need for Reform - Hussein, Ahmed (AUC Knowledge Fountain, 2025)
This thesis advocates for the implementation of domestic violence legislation in Egypt as a crucial legal and judicial reform necessary to prevent such violence and challenge societal norms that normalize it. It first examines the evolution of domestic violence legislation in line with international human rights standards, highlighting its applications worldwide and the role of states to interfere in an aim to combat such violence. The arguments for and against explicit criminalization are analyzed, emphasizing how legal frameworks can alter social behaviors that normalize violence. Following this, the thesis will focus on Egypt's legal framework addressing domestic violence, showing how the lack of domestic violence legislation has created critical legal gaps that impede effective law enforcement and judicial responses. By treating domestic violence as a private matter, the current legal framework, particularly in criminal, family, and child laws, fails to provide sufficient prevention. This inadequacy is further compounded by patriarchal norms and misinterpretations of Shari’a, which shape law enforcement and judicial practices in ways that often justify domestic violence. The absence of such a criminal framework exacerbates risks for victims in Egypt, especially in impoverished and marginalized communities, where poverty and limited education perpetuate the cycle of violence and increase vulnerability to exploitation and further counter-violence. By linking legal, social, and economic factors, this thesis argues that specific legislation would enhance legal support and increase societal awareness, fostering protection and accountability as well as shifting the inappropriate cultural behavior that accepts domestic violence as justifiable.